2022
DOI: 10.5435/jaaosglobal-d-22-00055
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experience and Perspective on Medical Cannabis as an Alternative for Musculoskeletal Pain Management

Abstract: Introduction: The current rate of opioid prescription is disquieting because of their high abuse potential, adverse effects, and thousands of overdose deaths. This situation imposes urgency in seeking alternatives for adequate pain management. From this perspective, this study aimed to evaluate the experience and the perceived analgesic efficacy of medical cannabis in managing the pain associated with musculoskeletal conditions. Methods: A 28-question s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Nevertheless, high-quality data regarding cannabis use for pain management in Orthopedic surgery is scarce, indicating that more research is needed [ 21 , 22 ]. While research on the effectiveness of cannabis for pain management is still ongoing, some have reported significant improvements in their symptoms with its use [ 23 ]. In Canada, medical cannabis has been legal since 2001, and in 2018 Canada legalized the recreational use of cannabis, presenting a unique setting for cannabis research.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, high-quality data regarding cannabis use for pain management in Orthopedic surgery is scarce, indicating that more research is needed [ 21 , 22 ]. While research on the effectiveness of cannabis for pain management is still ongoing, some have reported significant improvements in their symptoms with its use [ 23 ]. In Canada, medical cannabis has been legal since 2001, and in 2018 Canada legalized the recreational use of cannabis, presenting a unique setting for cannabis research.…”
Section: Introductionmentioning
confidence: 99%
“…7 Studies examining individuals' perspectives on cannabis for chronic pain have found that many who used medical cannabis consider it useful for pain relief. [8][9][10] However, there is limited information on the values and preferences of PLwCP in Canada, including how they weigh benefits and drawbacks of cannabis use, barriers and facilitators faced in the use of medical cannabis, decisions made regarding routes of administration and types of products used, sources where cannabis is obtained, and sources of information regarding cannabis for chronic pain. Incorporating such values and preferences into guidelines can improve the trustworthiness of recommendations and may lead to better outcomes for people living with chronic pain by promoting productive conversations and shared decision-making between individuals and providers.…”
Section: Introductionmentioning
confidence: 99%